2015
DOI: 10.17770/sie2015vol4.337
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Education in Promoting Social Innovation Processes in the Society

Abstract: <em>The<strong> </strong>purpose of the paper<strong> </strong>is to</em> <em>clarify the role of education in promoting social innovation processes in the society based on the main findings of the theoretical study conducted from October 2014 to January 2015 within the project “Involvement of the Society in Social Innovation for Providing Sustainable Development of Latvia” supported by the National Research Program 5.2.</em><strong> </strong><em&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The gap between pro-environmental attitudes to actual changes in behaviour has proven difficult to bridge, with reports of high levels of pro-environmental attitudes not necessarily corresponding to equally high levels of pro-environmental behaviours. Nevertheless, changes in attitudes are important, and this is where education for sustainability may also play an important role [28][29][30]. Orion and Libarkin suggested that the focus of the traditional environmental movement on the development of environmental awareness has failed to change the environmental behaviour of citizens worldwide and pointed to the inherent potential of Earth sciences to better address the challenge of changing environmental behaviour [31].…”
Section: Earth Sciences and Education For Sustainabilitymentioning
confidence: 99%
“…The gap between pro-environmental attitudes to actual changes in behaviour has proven difficult to bridge, with reports of high levels of pro-environmental attitudes not necessarily corresponding to equally high levels of pro-environmental behaviours. Nevertheless, changes in attitudes are important, and this is where education for sustainability may also play an important role [28][29][30]. Orion and Libarkin suggested that the focus of the traditional environmental movement on the development of environmental awareness has failed to change the environmental behaviour of citizens worldwide and pointed to the inherent potential of Earth sciences to better address the challenge of changing environmental behaviour [31].…”
Section: Earth Sciences and Education For Sustainabilitymentioning
confidence: 99%
“…Ultimately, social entrepreneurship is manifested when an individual is not isolated but rather is embedded into the structural environment and context (Vogel, 2017). This situation may arise when individuals and institutions, as agents of change, are enrolled in a comprehensive and structural social entrepreneurship development and education program (Surikova et al, 2015).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…environmental condition and developed and enhance individual's knowledge, skills and competencies [40].…”
Section: Csrmentioning
confidence: 99%